2014
DOI: 10.1253/circj.cj-13-1147
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Long-Term Outcome After Endovascular Therapy Versus Bypass Surgery in Claudication Patients With Trans-Atlantic Inter-Society Consensus-II C and D Femoropopliteal Disease

Abstract: on behalf of the RECANALISE Registry Investigators Background: Although endovascular therapy (EVT) has advanced, few reports have compared EVT and bypass surgery in claudication patients with femoropopliteal disease. The present study used data from a multicenter registry in Japan to analyze outcomes of EVT and bypass surgery for claudication patients with Trans-Atlantic InterSociety Consensus (TASC)-II C and D femoropopliteal lesions. Methods and Results:Of 1,156 patients who underwent revascularization, 696 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 29 publications
4
35
1
2
Order By: Relevance
“…Recently, the popularity of EVT has spread due to the associated lower morbidity and mortality rates, shorter hospital stay, and quicker recovery to normal functional status compared with surgical revascularization. 20, 21 EVT for the CFA, however, has been abandoned due to its unique characteristics: CFA lesions are too bulky and highly calcified to treat with balloon angioplasty, and surgeons hesitate to implant the stent because of the theoretical risk of stent fracture, sacrifice of DFA or preclusion from the CFA puncture. Frequently, restenosis appears following EVT for the CFA: the 1-year restenosis rate is 15-28%.…”
Section: Kuma S Et Almentioning
confidence: 99%
“…Recently, the popularity of EVT has spread due to the associated lower morbidity and mortality rates, shorter hospital stay, and quicker recovery to normal functional status compared with surgical revascularization. 20, 21 EVT for the CFA, however, has been abandoned due to its unique characteristics: CFA lesions are too bulky and highly calcified to treat with balloon angioplasty, and surgeons hesitate to implant the stent because of the theoretical risk of stent fracture, sacrifice of DFA or preclusion from the CFA puncture. Frequently, restenosis appears following EVT for the CFA: the 1-year restenosis rate is 15-28%.…”
Section: Kuma S Et Almentioning
confidence: 99%
“…However, since it has been recently reported that device and technical developments provide high recanalization rates 3) . Comparing with F -P bypass, in a recent report 1) , the Fig. 3C 82.1% and 69.4% in the bypass surgery and 67.8% and 45.2% in the EVT in claudication patients with TASC C and D, respectively.…”
Section: Discussionmentioning
confidence: 78%
“…We discussed with cardiovascular surgeons regarding indication of revascularization therapy. Comparing femoro -popliteal (F -P) bypass using the vascular graft, it has been reported that the initial success rate and secondary patency rate of EVT are close to F -P bypass 1) . Furthermore, the overall complication is higher in the F -P bypass than in EVT in claudication patients with Trans -Atlantic Inter -Society Consensus 44 Y. NAKAMURA et al…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…1) The primary success rate of EVT for SFA CTO has improved from 75% in 2001 2) to 81%-94% in 2014. 3) EVTs for SFA are generally managed by the antegrade approach, which uses a contralateral retrograde puncture or ipsilateral antegrade puncture of the common femoral artery. Alternatively, the popliteal approach is less frequently utilized.…”
mentioning
confidence: 99%